Network Enterprises The Evolution of Organizational Models from Guilds to Assembly Lines to Innovation Clusters - Dioguardi, Gianfranco. (Innovation, Technology, and Knowledge Management, 2010)
Building on the historical analysis of organizations and theories that have influenced their development, Gianfranco Dioguardi provides an insightful exploration of the network enterprise and its evolution from the Medieval guilds to the present innovation clusters of Silicon Valley, the Research Triangle, Route 128, and other regions in the U.S and around the world. Providing in-depth analysis of production systems and the evolution of "lean manufacturing" principles, Dioguardi integrates history, sociology, management theory, and economics to explore the dynamics of organizations that operate as networks and interact with other firms along the supply chain and in complementary industries. In a technology-enabled environment, the boundaries between products and services and across enterprises become blurredand create the context for entrepreneurship, innovation, and dissemination of knowledge. Several chapters are devoted to practical concerns of managing the network enterprise, with a particular interest in the ethical and cultural issues. Dioguardi concludes with discussion of the role of the network enterprise in new firm creation and economic growth.